Inhibition of Daxx-Mediated Apoptosis by Heat Shock Protein 27 - Charette, Steve J. (American Society for Microbiology, 2000)
Heat shock protein 27 (HSP27) confers cellular protection against a variety of cytotoxic stresses and also against physiological stresses associated with growth arrest or receptor-mediated apoptosis. Phosphorylation modulates the activity of HSP27 by causing a major change in the supramolecular organization of the protein, which shifts from oligomers to dimers. Here we show that phosphorylated dimers of HSP27 interact with Daxx, a mediator of Fas-induced apoptosis, preventing the interaction of Daxx with both Ask1 and Fas and blocking Daxx-mediated apoptosis. No such inhibition was observed with an HSP27 phosphorylation mutant that is only expressed as oligomers or when apoptosis was induced by transfection of a Daxx mutant lacking its HSP27 binding domain. HSP27 expression had no effect on Fas-induced FADD- and caspase-dependent apoptosis. However, HSP27 blocked Fas-induced translocation of Daxx from the nucleus to the cytoplasm and Fas-induced Daxx- and Ask1-dependent apoptosis. The observations revealed a new level of regulation of the Fas pathway and suggest a mechanism for the phosphorylation-dependent protective function of HSP27 during stress and differentiation.